Public Spending and Poverty Reduction in Indonesia: The Effects of Economic Growth and Public Spending on Poverty Reduction in Indonesia 2009-2018 - Hendrawan Toni Taruno (Department of Urban and Regional Planning, Universitas Diponegoro, 2019)
Poverty is a complex and multidimensional issue. Over the past four decades, the number of poor in Indonesia has experienced a significant decline, from 40.10 percent in 1976 to 9.82 percent in March 2018. Nevertheless, the disparity of poverty rates between provinces is still quite high. The poverty rate in several provinces in Java Island, for example, is already at the single-digit level, while in Eastern Indonesia, is still more than double-digit level. As it is known, public spending and economic growth are two crucial instruments on poverty reduction programs. This study aims to investigate the role of economic growth and public spending, particularly education, health, and social protection on poverty reduction in Indonesia. By using panel data from 31 provinces during 2009-2018 period, this study used two regression models to analyze the effects of these two variables on poverty reduction, both in urban and rural areas. This study shows that public spending on health and education sectors has a slightly different effect on poverty reduction between urban and rural areas. Convincingly, spending allocation on health and education has had a significant effect to reduce poverty rate in rural areas, while the decline of poverty rates in urban is likely more influenced by spending on health. This study also shows that over the past ten years, economic growth and social protection spending did not have a significant effect on reducing poverty rates. Therefore, in order to reduce poverty more effectively, it would be better for the government to focus its poverty reduction programs on investment in health and education sectors.